Sediment Content in Antarctic Iceberg Fragments Sufficient to Sink the Ice - Gilbert, Robert; Domack, Eugene; Tewksbury, David (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractIceberg fragments recovered from the sea floor near Swift Glacier, Antarctica, contained sufficient sediment to sink the ice. Sediment concentrations in the samples would have caused them to settle at 0.13 to 0.35 m/s through the water column. Impact with the sea floor would significantly turbate soft sediments. Unlike sediment dumped from icebergs, the stratigraphy of the frozen sediments created by glacial processes may be preserved in the marine sedimentary record after melting of the ice. Negatively buoyant berg fragments may be common in polar regions, and when driven by currents may scour the sea floor up and down slopes unlike floating ice.